Electron shuttle-dependent biofilm formation and biocurrent generation: Concentration effects and mechanistic insights - Zhu, Xiao; Dou, Fei; Long, Mingliang; Wang, Xinxin; Liu, Wei; Li, Fangbai; Liu, Tongxu; Wu, Yundang (Frontiers in Microbiology, 2023)
Electron shuttles (ESs) play a key role in extracellular electron transfer (EET) in Shewanella oneidensis MR-1. However, the quantification relationship between ES concentration, biofilm formation, and biocurrent generation has not been clarified. In this study, 9,10-anthraquinone-2-sulfonic acid (AQS)–mediated EET and biofilm formation were evaluated at different AQS concentrations in bioelectrochemical systems (BESs) with Shewanella oneidensis MR-1. Both the biofilm biomass (9–17 folds) and biocurrent (21–80 folds) were substantially enhanced by exogenous AQS, suggesting the dual ability of AQS to promote both biofilm formation and electron shuttling. Nevertheless, biofilms barely grew without the addition of exogenous AQS, revealing that biofilm formation by S. oneidensis MR-1 is highly dependent on electron shuttling. The biofilm growth delayed in BES of 2000 uM AQS, which is because the redundant AQS in the bulk solution acted as a soluble electron acceptor and delayed the attachment of cells to the electrode. In addition, the maximum biocurrent density in BESs with different concentrations of AQS was fitted to the Michaelis–Menten equation (R2 = 0.97), demonstrating that the microbial-catalyzed ES bio-reduction is the key limiting factor of the maximum biocurrent density in BESs. This study provided a fundamental understanding of ES-mediated EET, which could be beneficial for the enrichment of electroactive biofilms, the rapid start-up of microbial fuel cells, and the design of BESs for wastewater treatment.